Hubungan Tingkat Stres, Kebiasaan Konsumsi Fast Food dengan Status Gizi pada Remaja - Syahrainy, Syahrainy; Khasana, Tri Mei; Septriana, Septriana (Poltekkes Kemenkes Mataram, 2023)
Background: One of the main health indicators of a country is nutritional status. There are various factors that can influence nutritional status, one of which is stress levels and fastfood consumption habits, excessive stress levels and consuming fast food too often will have an impact on changes in a person's nutritional status, which will then pose a risk of health problems in the future. Objective: To determine the relationship between stress levels, fast food consumption habits and nutritional status of adolescents at SMAN 1 Kalasan Yogyakarta. Methods: This research uses a cross-sectional design, with a proportional random sampling technique, the number of research respondents was 77 respondents. Weight and height measurement data is carried out directly to determine nutritional status (BMI/U), stress levels were measured using the DASS questionnaire, fast food consumption habits using the fastfood consumption habit questionnaire form. Data analysis used univariate and bivariate tests with the Chi-Square test. Results: There were 57,1% of adolescents with normal nutritional status, 51,9% of adolescents with stress levels in the no-stress category, 50,6% of adolescents with frequent fast food consumption habits. The results showed that there was no relationship between stress levels and the nutritional status of adolescents (p-value = 0,449). There was no relationship between the habit of consuming fast food and the nutritional status of adolescents (p-value = 0,576). Conclusion: There is no relationship between stress levels, fast food consumption habits and nutritional status of adolescents at SMAN 1 Kalasan Yogyakarta.